Does Foreign Capital Really Matter for Employment? Evidence from Agricultural Dominance African Countries - Poumie, Boker; Claude, Dounya Matsop (Asian Journal of Economic Modelling, 2021)
This paper examines the impacts of foreign capitals (FDI, migrant remittances, and agricultural aid) on overall and sectoral employment using a simple labor demand model for a panel of 43 African countries from 2002 to 2018. Our econometric investigation reveals the presence of cross-section dependence and a long-run relationship among variables. Using the dynamic ordinary least square (DOLS), the augmented mean group (AMG), and the common correlated effects means group (CCEMG) methods, we find that only migrant remittances and FDI positively affect total employment. Still, FDI has a positive significant effect on agriculture, industry, and service employment. Our findings also indicate that migrant remittances reduce employment in agriculture and increase job creation in the service and industry sectors. Finally, aid to agriculture does not contribute to job creation in African countries and even negatively affects industry employment. This study supports the view that migrant remittances contribute to transforming the employment structure in Africa countries. Some recommendations are proposed.